The risk of hyperuricemia assessed by estimated glucose disposal rate - Zhaoxiang Wang; Ruoshuang Liu; Fengyan Tang; Yirong Shen (Frontiers in Endocrinology)
PurposeThe estimated glucose disposal rate (eGDR) is a simple and noninvasive clinical measure used to assess insulin resistance (IR), yet its potential utility as a marker for hyperuricemia risk had not been systematically evaluated. This study aimed to investigate the relationship between eGDR and hyperuricemia risk among American adults.MethodsData for this cross-sectional study were obtained from the 2007–2018 National Health and Nutrition Examination Survey (NHANES). Hyperuricemia was identified as a serum urate (SU) concentration of ≥7 mg/dL in males and ≥6 mg/dL in females. The relationship between eGDR and hyperuricemia risk was assessed using multivariate logistic regression and restricted cubic spline (RCS) methods, with additional subgroup and interaction analyses performed.ResultsWith increasing eGDR values, the prevalence of hyperuricemia decreased significantly (29.93% vs. 19.11% vs. 13.20% vs. 5.03%, P<0.001). Multivariate logistic regression indicated that eGDR was independently associated with the risk of hyperuricemia after controlling for covariates including demographic, lifestyle, and clinical factors (OR=0.93, 95%CI: 0.90-0.96, P<0.001). RCS analysis further revealed a nonlinear relationship, with a turning point at eGDR 7.96 mg/kg/min. Subgroup analysis revealed a stronger inverse association between eGDR and hyperuricemia risk in females.ConclusionsThe eGDR is inversely associated with hyperuricemia and appears to be a promising epidemiological tool for evaluating the impact of IR on the risk of hyperuricemia.